Sunscreen Activity of Soursop Seeds Extract - Erlien Dwi Cahyani; Antonius Budiawan; Levi Puradewa (Universitas STRADA Indonesia, 2022)
Indonesia is a tropical climate country that is rich in sunlight. Sunlight overexposure leads to skin damage such as sunburn, black spots, wrinkles, and aging skin which is caused by oxidative stress. Soursop is a fruit rich in flavonoids that has the antioxidant activity to prevent oxidative stress and is known for its sunscreen effect. This study was aimed to determine the sunscreen activity of soursop seed extract by Sun Protective Factor (SPF) parameter. Soursop extract divided to 0.15 and 0.25% concentration and the SPF value was measured quantitatively using Spectrophotometer UV-Vis. SPF measurement result showed that soursop seeds extract 0.15 and 0.25% concentration gives 4.35 and 7.38 respectively SPF value. Soursop seeds extract showed sunscreen activity with low protection category.